Answer: the slope would be 0
Step-by-step explanation:
Answer:
<h2>

</h2>
Step-by-step explanation:
f(x) = 2x + 4
g(x) = 4x² + 1
In order to find (g ∘ f)(0) we must first find
(g ° f )(x)
To find (g ° f )(x) substitute f(x) into g(x) that's for every x in g(x) replace it with f(x)
That's
<h3>

</h3>
We have
<h3>

</h3>
Now to find (g ∘ f)(0) substitute the value of x that's 0 into (g ∘ f)(0)
We have
<h3>

</h3>
We have the final answer as
<h3>

</h3>
Hope this helps you
Answer:
Attached Image
Step-by-step explanation:
Vertex: (5, -5)
X-Intercepts: (1,0) (9,0)
Y-Intercepts: (0, 2.813)
hope this helps :)
Answer:
The final result is 1
Step-by-step explanation:
Remember the following:

And that x^0= 1
We have: 8^7 / 8^7= 8 ^ (7-7)=8^0=1